A Novel Technology for the Recovery of Zinc from the Zinc Leaching Residue by the Bottom-blown Reduction. (18th August 2021) - Zhang, Zhongtang; Li, Weifeng; Zhan, Jing; Li, Gui; Zhao, Zhenbo; Hwang, Jian-Yang
ABSTRACT: Zinc leaching residue is an important secondary sources of zinc. To realize recycling utilization of this zinc secondary resource, a novel technology is proposed for the recovery of zinc from the zinc leaching residue by the bottom-blown reduction process in this study. The effects of reduction temperature, reduction time, coal rate, and lime addition on the metal content in the slag and the volatilization rate of lead and zinc during reduction were evaluated. The optimized conditions for the recovery of Pb and Zn in the bottom-blown reduction process were determined as 1473 K with a coal rate of 35% and a lime addition of 4% for a reduction time of 70 min. Under the optimized conditions, the recovery rate of Pb and Zn is over 90% and 94%, respectively. The lead, zinc, and copper content in the reduced slag is 0.15%, 0.7%, and 0.07%, respectively. An industrial test was carried out for the recovery of Pb and Zn from the zinc leaching residue by bottom-blown reduction, resulting in a ZnO content of less than 3% in the reduced slag and a coal rate of 35%, not less than 0.6 for CaO/SiO2 (mass ratio) and 1.0 1.2 for FeO/SiO2 (mass ratio).